Environmental influences on speleothem growth in southwestern Oregon during the last 380 000 years - Ersek, V; Hostetler, S; Cheng, H; Clark, P; Anslow, F; Mix, A; Edwards, R (2009)
The growth of carbonate formations in caves (speleothems) is sensitive to changes in environmental conditions at the surface (temperature, precipitation and vegetation) and can provide useful paleoclimatic and paleoenvironmental information. We use 73 230Th dates from speleothems collected from a cave in southwestern Oregon (USA) to constrain speleothem growth for the past 380 000 years. Most speleothem growth occurred during interglacial periods, whereas little growth occurred during glacial intervals. To evaluate potential environmental controls on speleothem growth we use two new modeling approaches: i) a one-dimensional thermal advection-diffusion model to estimate cave temperatures during the last glacial cycle, and ii) a regional climate model simulation for the Last Glacial Maximum (21 000 years before present) that assesses a range of potential controls on speleothem growth under peak glacial conditions. The two models are mutually consistent in indicating that permafrost formation did not influence speleothem growth during glacial periods. Instead, the regional climate model simulation combined with proxy data suggest that the influence of the Laurentide and Cordilleran ice sheets on atmospheric circulation induced substantial changes in water balance in the Pacific Northwest and affected speleothem growth at our location. The overall drier conditions during glacial intervals and associated periods of frozen topsoil at times of maximum surface runoff likely induced drastic changes in cave recharge and limited speleothem growth. This mechanism could have affected speleothem growth in other mid-latitude caves without requiring the presence of permafrost. © 2009 Elsevier B.V.